Nomenclatural notes in the Pleurothallidinae (Orchidaceae): Stelis - Karremans Lok, Adam Philip (2015)
Nomenclatural changes are made in order to place within Stelis a series of species that belong to it in the sense of Genera Orchidacearum, and without previous available names in that genus. New species, names and combinations are proposed, a short discussion for the reasoning is given.